Sustainable Development through Youth Innovation: A Case for Scientific Collaboration in Addressing Climate Challenges in West Africa - Thomas Sheku Marah (Marasofi International Media and Publishing (MIMP), 2025)
West Africa faces escalating climate challenges that threaten socio-economic stability and ecological balance. Traditional mitigation strategies have largely excluded the youth, despite their increasing engagement and innovative capacities. This study explores the potential of youth-led climate initiatives in Sierra Leone, Ghana, and Nigeria, emphasizing the role of scientific collaboration in enhancing their impact. Using a qualitative approach with secondary data from 2020–2024, the research applies thematic analysis framed by the Innovation Ecosystem Model and the co-creation concept within the SDG framework (SDG 13 and SDG 17). Findings show that youth innovations—such as renewable energy projects, climate-smart agriculture, and digital tools—gain greater legitimacy, scale, and policy relevance when connected with academic and institutional partners. However, barriers persist, including limited funding, weak infrastructure, and marginalization in formal governance. The study recommends institutionalizing youth-science partnerships, establishing climate innovation grants, integrating youth in national adaptation plans, enhancing digital infrastructure, and supporting gender-responsive innovation. Strengthening these frameworks is vital to harnessing West Africa’s demographic potential and ensuring sustainable, climate-resilient development.